2005
DOI: 10.4049/jimmunol.174.9.5490
|View full text |Cite
|
Sign up to set email alerts
|

Loss of New Chemokine CXCL14 in Tumor Tissue Is Associated with Low Infiltration by Dendritic Cells (DC), while Restoration of Human CXCL14 Expression in Tumor Cells Causes Attraction of DC Both In Vitro and In Vivo

Abstract: Breast and kidney-expressed chemokine (BRAK) CXCL14 is a new CXC chemokine with unknown function and receptor selectivity. The majority of head and neck squamous cell carcinoma (HNSCC) and some cervical squamous cell carcinoma do not express CXCL14 mRNA, as opposed to constitutive expression by normal oral squamous epithelium. In this study, we demonstrate that the loss of CXCL14 in HNSCC cells and at HNSCC primary tumor sites was correlated with low or no attraction of dendritic cell (DC) in vitro, and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(150 citation statements)
references
References 37 publications
5
143
2
Order By: Relevance
“…Second, we have recently reported that the lost expression of chemokine CXCL14 in human SCCHN tumors may be associated with decreased attraction of DC to the tumor site and, thus, may also be associated with deficient induction of antitumor immune responses [54]. The important role of CXC14 in attraction of immature DC and DC precursors to normal tissues has been also confirmed by others [67,68].…”
Section: Tumor-associated Dendritic Cellmentioning
confidence: 91%
See 3 more Smart Citations
“…Second, we have recently reported that the lost expression of chemokine CXCL14 in human SCCHN tumors may be associated with decreased attraction of DC to the tumor site and, thus, may also be associated with deficient induction of antitumor immune responses [54]. The important role of CXC14 in attraction of immature DC and DC precursors to normal tissues has been also confirmed by others [67,68].…”
Section: Tumor-associated Dendritic Cellmentioning
confidence: 91%
“…It has been recently demonstrated that many tumor cell lines loss the expression of CXCL14 [125]. We and other reported that CXCL14 is a potent chemoattractant for immature DC [54,67] suggesting that loss expression of CXCL14 at the tumor site might be responsible, at least in part, for low attraction of DC and thus deficient initiation of antitumor immune responses.…”
Section: Regulation Of Intratumoral Dendritic Cells By Cytokines Chementioning
confidence: 95%
See 2 more Smart Citations
“…CXCL14 is further expressed in several immune cell types, such as immature dendritic cells (iDCs), monocyte-derived dendritic cells (DCs), activated B-cells and activated isolated human monocytes [14-16]. CXCL14 is known to act as a chemotactic agent for human B-cells, THP-1 cells, activated human natural killer cells (NKs), human and murine iDCs as well as human monocytes [12, 13, 16-19]. Cutaneous CXCL14 is involved in the recruitment of CD14 + DC precursors and in driving their differentiation into Langerhans cells [13].…”
Section: Introductionmentioning
confidence: 99%